Thermocatalytic routes and reactor strategies for valorization of biodiesel-derived glycerol to fuels. (September 2022) - Okoye, P.U.; Arias, D.M.; Hameed, B.H.; Sebastian, P.J.; Li, Sanxi; Song, Wang
Graphical abstract: Highlights: Reactor strategies and thermochemical routes to valorize glycerol to fuels were reviewed. More than 70% hydrogen could be obtained from glycerol reforming. Fluidized bed, downdraft, and up-flow fixed bed reactors are often used. Coking and sintering are deactivation mechanisms encountered by Ni-based catalysts. Circulating fluidized bed reactor allows catalyst self-regeneration. Abstract: Glycerol is an oversupplied commodity from biodiesel production with beneficial properties for the synthesis of versatile utility biochemicals. The functional properties of glycerol with three hydroxyl groups could be tailored toward producing fuels such as hydrogen, syngas, C1 -C3 hydrocarbon fuel, bio-oil and methane. This study elucidates the reported thermochemical pathways such as pyrolysis, gasification, combustion, steam and aqueous reforming, and supercritical water gasification for fuel production from biodiesel-derived glycerol. The mechanism of these pathways, process conditions, catalytic integration, and limitations were investigated. Also, reactor strategies such as fixed bed reactors, fluidized bed, and solar reactor strategies used for the thermochemical valorization of glycerol was discussed. The studies revealed that hydrogen up to 70% yield could be generated from glycerol using noble metals and nickel-based catalysts. Catalyst deactivation due to coking could be minimized by the addition of alkaline metals, which discourages methanation reaction. Reaction parameters such as temperature, catalyst amount, time on stream, and glycerol/water or steam ratio influence the product distribution. The glycerol steam reforming is more energy-intensive and requires temperatures in the range of 450–1000 °C, whereas the aqueous reforming is propagated in the range of 180–250 °C. The circulating fluidized bed reactors limit coking due to self-regeneration of the catalysts in situ, however, they are cost-intensive. Life cycle assessment analysis revealed that supercritical water reforming (SCWR) of glycerol offers a sustainable pathway to reduce CO2 by 95% and integration of SCWR in biodiesel plants to produce hydrogen for heating can realize a net present value between 7.70 and 15.70 million USD. Further studies to analyze the economic impact of the individual pathways to optimize the production of fuels from glycerol are required. It is hoped that this study will engage industries and researchers to increasingly use glycerol as a substrate for the production of fuels for transportation.